DRIVER OF ECONOMIC GROWTH-INVESTMENT, INNOVATION AND SCIENTIFIC TECHNOLOGIES (Scientific journal of the Fergana State University, 2023)
This article discusses the problems of scientific analysis of the practical organization of free economic zones and the use of its results for the further development of science, new technologies with the effective use of investments as a driver of innovative development in Uzbekistan.